Respuesta :

Answer:

x=-1

y=-5

Step-by-step explanation:

(7x+y)-(x+y)=-6

6x=-6

x=-1

-1+y=-6

y=-5

Answer:

(-1, -5)

Step-by-step explanation:

Solve x + y = -6 for x

  • [tex]x + y = -6[/tex]

Subtract y from both sides.

  • [tex]x + y - y = -6 - y[/tex]
  • [tex]x = -y - 6[/tex]

Substitute -y - 6 for x in 7x + y = -12

  • [tex]7(-y-6)+y=-12[/tex]

Simplify both sides.

  • [tex]-6y - 42 = -12[/tex]

Add 42 to both sides.

  • [tex]-6y - 42 + 42 = -12 + 42[/tex]
  • [tex]-6y = 30[/tex]

Divide both sides by -6.

  • [tex]\frac{-6y}{-6} = \frac{30}{-6}[/tex]
  • [tex]y = -5[/tex]

Substitute -5 for y in x = -y - 6

  • [tex]x = -(-5) -6[/tex]

Simplify both sides of the equation.

  • [tex]x = 5 - 6[/tex]
  • [tex]x = -1[/tex]

Therefore, the answer is (-1, -5).